UR‐144 in products sold via the Internet: Identification of related compounds and characterization of pyrolysis products. Issue 8 (11th January 2013) - Kavanagh, Pierce; Grigoryev, Andrej; Savchuk, Sergey; Mikhura, Irina; Formanovsky, Andrew
<x xml:space="preserve">Abstract</x> The synthetic cannabinoid, UR‐144 ((1‐pentyl‐1H‐indol‐3‐yl)(2, 2, 3, 3‐tetramethylcyclopropyl)methanone), was identified in commercial 'legal high' products (herbal, resin, and powder). Along with this, six related compounds were detected. The most abundant one (2.1) was identified as 4‐hydroxy‐3, 3, 4‐trimethyl‐1‐(1‐pentyl‐1H‐indol‐3‐yl)pentan‐1‐one, a product of the electrophilic addition of water to the cyclopropane moiety in UR‐144. Compound 2.1 was found to be undergo cyclisation which leads to the formation of two additional interconvertable compounds (2.3, tentatively identified as 1‐pentyl‐3‐(4, 4, 5, 5‐tetramethyl‐4, 5‐dihydrofuran‐2‐yl)‐1H‐indole which is stable only in absence of water and also observed as GC artifact) and 2.2, a protonated derivative of 2.3 which is formed in acidic solutions. The remaining compounds were identified as possible degradation products of the group 2 compounds (4, 4, 5, 5‐tetramethyldihydrofuran‐2(3H)‐one and 1‐pentylindoline‐2, 3‐dione) and intermediates or by‐products from the synthesis of UR‐144 ((1H‐indol‐3‐yl)(2, 2, 3, 3‐tetramethylcyclopropyl)methanone, 1‐pentyl‐1H‐indole and 1‐(1‐pentyl‐1H‐indol‐3‐yl)hexan‐1‐one). Pyrolysis of herbal products containing the group 2 compounds or UR‐144 resulted in the formation of 3, 3, 4‐trimethyl‐1‐(1‐pentyl‐1H‐indol‐3‐yl)pent‐4‐en‐1‐one (3). This was confirmed by separate pyrolysis of 2.1 and UR‐144. Also, the two additional minor compounds, 1‐(1‐pentyl‐1H‐indol‐3‐yl)ethanone and 1‐(1‐pentyl‐1H‐indol‐3‐yl)propan‐1‐one, were detected. Pathways for these transformations are presented. Copyright © 2013 John Wiley & Sons, Ltd.